1996
DOI: 10.1093/ajcn/64.5.772
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity in elderly men is enhanced by beta-carotene supplementation

Abstract: Natural killer (NK) cell activity has been postulated to be an immunologic link between beta-carotene and cancer prevention. In a cross-sectional, placebo-controlled, double-blind study we examined the effect of 10-12 y of beta-carotene supplementation (50 mg on alternate days) on NK cell activity in 59 (38 middle-aged men, 51-64 y; 21 elderly men, 65-86 y) Boston area participants in the Physicians' Health Study. No significant difference was seen in NK cell activity due to beta-carotene supplementation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
2
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 21 publications
5
76
2
5
Order By: Relevance
“…Immune enhancement by B. lactis B-L Chiang et al are important indices of innate (`natural') immunity, and are commonly employed to gauge the capacity of dietary interventions to stimulate the immune system (Schiffrin et al, 1995;Santos et al, 1996). The present observations con®rm results from a previous clinical trial, which had demonstrated enhanced peripheral blood cell phagocytic activity and production of the cytokine interferon-alpha among elderly subjects (aged 60 ± 83 y) following consumption of B. lactis (Arunachalam et al, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…Immune enhancement by B. lactis B-L Chiang et al are important indices of innate (`natural') immunity, and are commonly employed to gauge the capacity of dietary interventions to stimulate the immune system (Schiffrin et al, 1995;Santos et al, 1996). The present observations con®rm results from a previous clinical trial, which had demonstrated enhanced peripheral blood cell phagocytic activity and production of the cytokine interferon-alpha among elderly subjects (aged 60 ± 83 y) following consumption of B. lactis (Arunachalam et al, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…An increase in the percentage NK cells was reported in a non-controlled trial of men aged 35 ± 79 with either oral leukoplakia or Barrets oesophagus, who were supplemented with 30 mg b-carotene daily for 3 months . In contrast, several controlled studies in healthy young or elderly volunteers have reported no effect of supplementation with b-carotene (Ringer et al, 1991;van Poppel et al, 1993;Daudu et al, 1994;Santos et al, 1996), or indeed vitamin E (Meydani et al, 1995), on lymphocyte subsets. The results from the studies of disease groups should be interpreted with care, bearing in mind the dif®culty in controlling these trials adequately.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have shown that the immune response of healthy elderly volunteers is also enhanced by supplements containing dietary antioxidants (Meydani et al, 1990;Chandra, 1992;Santos et al, 1996).…”
Section: Cd3mentioning
confidence: 99%
“…Santos et al (127) showed that neither short-term, high-dose (90 mg/day for 3 weeks) nor long-term, moderate-dose (50 mg every 2 days for 12 years) supplementation with β-carotene had a significant effect on in vitro or in vivo indices of T cell-mediated function. However, longterm β-carotene supplementation did increase natural killer cell activity in older people (128).…”
Section: Vitamin Ementioning
confidence: 87%